Reading and other guilty pleasures: Human misconduction in the discourse of disciplinary action (KULT_online, 2014)
This anthology contains exemplary text from the18th to 20th century, dealing with various habitual discourses. Bernhard Kleeberg, professor at the University of Konstanz, argues that there is a significant presence of habitual discourses in the chosen period. Such discourses should serve to discipline others as well as oneself and to protect cultural norms and ideals. Kleeberg provided the chosen texts in a chronological order. Each example is followed by a comment of an author from the field of cultural studies in order to clarify its historical background and the corresponding discourses.